USAGE OF DIFFERENT STYLISTIC TROPES IN ENGLISH AND UZBEK LANGUAGES AND THEIR SPECIFIC CHARACTERISTICS (Academicia Globe: Inderscience Research, 2022)
Expressive means of language and stylistic tropes are one of the main parts of linguistics. This field has its own characteristics in each language. In this article, we compare the main features of stylistic devices and tropes in English and Uzbek. Expressive devices and stylistic tropes are one of the main parts of linguistics. This field has its own characteristics in each language. In this article, we will compare the main features of stylistic devices and tropes in English and Uzbek.